FORMULASI PAKAN KUDA PEJANTAN HANOMAN YR PADA PETERNAKAN KUDA TOMBO ATI STABLE SALATIGA - , GIOVANI MEYRZA OKA P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The on the job training at horse ranch in Tombo Ati Stable purposed to learning the horse feed nutritional contents of male horse Hanoman Yr at Tombo Ati Stable horse ranch and studying the making of horse feed and the way of feeding a male horse. In Tombo Ati horse ranch that breed the race horse. The feeding material that given to male Hanoman Yr horse is horse feed that produced by Putri Gunung Farm, Bogor (Extrapro and Athleto). The method that use is direct observation, data taking and do the practicing in field work like: preparation of stable tool, stable place and horse feed, horse feed giving and horse care. Based on the result of on the job training at horse ranch in Tombo Ati Stable, Gintungan, Tengaran, Semarang can be concluded that horse feed formulation has been proven that accomplished the normal standard of energy needs that digested in male Hanoman Yr.